2011
DOI: 10.1017/s146342361100051x
|View full text |Cite
|
Sign up to set email alerts
|

What are the patient-held illness beliefs after a transient ischaemic attack, and do they determine secondary prevention activities: an exploratory study in a North London General Practice

Abstract: The traditional medical definition of TIA and stroke do not reflect the views of patients who have had TIAs. One's perception of the severity of the initial TIA event and the risk of future stroke episodes may influence the uptake of secondary stroke prevention activities. Post TIA stroke prevention interventions should include tailored discussions focussing on the importance of the acute event and its implications for long-term health and future stroke risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 21 publications
3
28
0
Order By: Relevance
“…Our response rate was similar to reported rates in other qualitative studies conducted with TIA patients [18]. Although, as in all research studies, it is possible that patients who choose to participate may differ from those that don't, participants in the current study did not differ in terms of gender and postcode index of multiple deprivation scores from those that did not take part.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our response rate was similar to reported rates in other qualitative studies conducted with TIA patients [18]. Although, as in all research studies, it is possible that patients who choose to participate may differ from those that don't, participants in the current study did not differ in terms of gender and postcode index of multiple deprivation scores from those that did not take part.…”
Section: Discussionsupporting
confidence: 82%
“…As with previous qualitative studies in TIA populations (e.g. [18]) participation in this study was limited to patients who did eventually seek care and had received a TIA diagnosis. Consequently, participants' recall of symptoms and care-seeking decisions may have been affected by the subsequent attachment of a TIA label to their experiences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the TIA changed participants’ perception of their health as they became aware of their stroke risk. Similarly Kamara & Singh also found a discrepancy between the medical definition of TIA as an acute event and the participant’s explanation of TIA which related to the ability to recover fully from the TIA in the long term [24]. We have identified the long term consequences of TIA for participants in our sample which included 13 people under 65 of whom seven were still in work and two were primary carers of young or disabled children.…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown that those who perceive TIA as something minor or with no lasting impact may be reluctant to address risk factors for further cerebrovascular events. 34 Identifying balance and walking problems may be one way to overcome this barrier.…”
Section: Discussionmentioning
confidence: 99%